Indicators of Bank Sustainability - Puspitasari, Devy M.; Febrian, Erie; Anwar, Mokhammad; Sudarsono, Rahmat; Napitupulu, Sotarduga (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to investigate the sustainability of rural banks in West Java, Indonesia. The method used is descriptive verification and panel data analysis while secondary data obtained from Bank reports during the period 2012 to 2016 were used. The population in this study includes rural banks in West Java and the sample selection is based on purposive sampling. From the results, it was shown that capital and liquidity risk have a significant influence on financial performance. Meanwhile, credit risk and operation efficiency have no significant influence on financial performance. Furthermore, a Credit distribution strategy is needed for the sustainability of banks and increase in efficiency also needs to be continuously considered by management to improve bank performance. This research will be useful for investigating the sustainability of rural banks in West Java using financial performance, which has not been conducted previously.